Magnetic treatment of brackish water for sustainable agriculture - Hassan, Kareem (AUC Knowledge Fountain, 2015)
Egypt and most of the MENA countries are suffering from physical water scarcity. The abundance of fresh water is very limited; consequently, it is needed to rethink about the use of non-conventional water resources as a source of water for agricultural purposes. This study investigated the influence of magnetic treatment on brackish water, and its application for sustainable agriculture practices. The experimental work was divided into four main categories: The first category was the physical analysis of magnetically treated brackish water; including surface tension investigation, salt solubility test, and nutrients solubility test. The second category was the chemical analysis; including TDS, pH, nutrients and dissolved oxygen. The third category was the application of magnetically treated brackish water on soil enhancement; including soil desalinization test, and nutrients release in soil. The fourth category was the application of magnetically treated brackish water for crops irrigation; including seed germination test, and pilot scale cultivation. The results of this study proved the positive influence of magnetic treatment on brackish water; it reduced the surface tension of brackish water by 26%, and this change in surface tension lasted for 2 days after magnetic treatment, in addition to the significant increase of salt and nutrients solubility. The chemical properties of water did not change significantly; nevertheless the dissolved oxygen of magnetically treated brackish water was increased significantly. The application of magnetic treatment of brackish water enhanced the soil desalinization up to 25% and increased the soil’s nutrient content in the plant root zone by 33-53%. The barely seeds irrigated with magnetically treated brackish water had a significant increase in germination rate up to 30%, and an increase in crop yield by 25%. The magnetic treatment of brackish water improved its quality and productivity for irrigation, which will open the door for different agricultural applications. Further studies and applications are needed in this field to come up with optimized design values for the key variables of magnetic treatment, leading to maximizing the benefits of the abundant brackish water in Egypt.